Using procalcitonin levels to predict infection and reduce unnecessary antibiotic usage in febrile children aged 3-36 months - Thongsamer, Piyanuch; Laoprasopwattana, Kamolwish (The Journal of Infection in Developing Countries, 2022)
Introduction: High risk features including body temperature (BT) ≥ 39 °C, inactive appearance, white blood cells (WBC) ≥ 15,000 cells/mm3, or absolute band count (ABC) ≥ 1,500 cells/mm3 have low sensitivity and negative predictive value (NPV) to discriminate between bacterial and viral infections, leading to overuse of antibiotics. We aimed to determine whether procalcitonin (PCT) level ≥ 0.5 ng/mL can differentiate bacterial from viral infections. Methodology: The medical data of children aged 3 to 36 months who presented with fever without localizing signs or having initially undetermined cause of respiratory tract infection and/or non-mucus bloody diarrhea for 1 to 7 days and were hospitalized between January 2017 and December 2018 with one of the high-risk features were recorded. Children with an immunocompromised condition, who had previously received antibiotics, and/or had clinical sepsis were excluded. Results: Non-serious bacterial infection (SBI) and SBI (occult bacteremia) were found in 17.2% and 4.5%, respectively. The proportions of children with high-risk features were not significantly different between children with and without bacterial infection, except for absolute band count which was significantly higher in the bacterial infection group (419 cells/mm3, IQR [0, 1429]) than the non-bacterial group (76 cells/mm3, IQR [0,455]). A PCT level ≥ 0.5 ng/mL had the highest sensitivity and NPV (100%, 100%, respectively) to predict bacterial infection when compared with the other high-risk features. Conclusions: Antibiotics can be safely withheld while waiting for hemoculture in acute febrile children with one of the high-risk features of bacterial infection with PCT level < 0.5 ng/mL.